1976
DOI: 10.1159/000152802
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Studies in Kerala and the Nilgiris (South West India)

Abstract: A total of nearly 1,000 persons belonging to a number of caste, religious and tribal groupings in Kerala and the Nilgiri Hills of South India have been tested for genetic variation in 4 blood group, 5 serum protein and 17 enzyme systems as well as haemoglobin. The distribution of blood groups, serum protein and enzyme groups is similar to that reported for other South Indian populations. Of particular interest is the presence of LDH ‘Calcutta-1 variants in three of the Hindu and Muslim communities, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 4 publications
4
23
2
Order By: Relevance
“…Omoto and Blake (1972) described a similar variant in a Chinese of Singapore. In the present investigation no variant of type 2-1 was found, but there are reports of one example in each of the nontribal groups of Andhra and a frequency of the P G I ~ allele of 1.2~ from Christians of Kerala (Ramesh et al, 1979(Ramesh et al, , 1980Saha et al, 1976). This suggests localisation of the allele to specific populations of south India.…”
Section: A) the P G I 2 Allelecontrasting
confidence: 55%
“…Omoto and Blake (1972) described a similar variant in a Chinese of Singapore. In the present investigation no variant of type 2-1 was found, but there are reports of one example in each of the nontribal groups of Andhra and a frequency of the P G I ~ allele of 1.2~ from Christians of Kerala (Ramesh et al, 1979(Ramesh et al, , 1980Saha et al, 1976). This suggests localisation of the allele to specific populations of south India.…”
Section: A) the P G I 2 Allelecontrasting
confidence: 55%
“…Jia et al (2005) reported an extremely low frequency of Pro7 in a Chinese population, although Duan et al (2005) failed to detect this allele in the same region. In our study, the highest frequency of this allele (0.23) was observed in the Kota (haplotype CGG frequency is 0.23) Since the Kota have been a small, isolated population for at least 2,000 years (Breeks 1873;Saha 1976;Roychoudhury et al 2001), the high frequency of Pro7 is likely due to a founder effect or genetic drift. The Pro7 allele is also found in the Siddi, who are a recent migrant group from Africa (haplotype CGG frequency is 0.017).…”
Section: Discussionsupporting
confidence: 42%
“…Highest frequency of Cal-1 type has been reported among the Kurumbas of Nilgiri Hill (Saha et al, 1976).…”
mentioning
confidence: 95%